Five Year Plan Assam District and Subdivisional Series Goalpara District - Government of Assam (Government of Assam, 1954)
The Assam Five-Year Plan (1951-56) for Goalpara District presents a detailed strategy for localized development aimed at improving socio-economic conditions and fostering sustainable growth. The plan encompasses general development initiatives, expansions, community projects, and Article 275 schemes, with a total expected expenditure of approximately ₹149.87 lakhs, of which ₹50.61 lakhs had been utilized in the first three years, reflecting effective fiscal management. Key objectives include enhancing agriculture through minor irrigation and improved tea garden land utilization, promoting community welfare via educational facilities, healthcare, and women’s programs, and stimulating local economic growth. Implementation is structured through subdivisional development committees, ensuring stakeholder participation and oversight, alongside systematic monitoring mechanisms to track progress against targets. Notable achievements by mid-1954 included the establishment of large-scale waterworks, vaccination programs, and improvements in agricultural productivity, highlighting a proactive approach toward addressing regional needs. Overall, the Five-Year Plan for Goalpara District exemplifies Assam’s commitment to balanced district-level development, emphasizing the integration of social welfare, economic advancement, and participatory governance to drive long-term regional progress.
Goalpara District
Goalpara District
Keywords: Assam Five-Year Plan; Goalpara District; Local Development; Agriculture; Minor Irrigation; Community Projects; Social Welfare; Health Infrastructure; Education; Tea Gardens; Development Committees; Public Health